Failure of aluminium self-piercing rivets: An experimental and numerical study - Hoang, N.-H.; Hopperstad, O.S.; Langseth, M.; Westermann, I. (Materials in engineering, 2013)
► We investigated the fracture mechanism of AA7278-T6 aluminium self-piercing rivets. ► Fracture of AA 7278-T6 rivets during the riveting process is a complex phenomenon. ► Microstructure of AA7278-T6 has significant influence on the fracture mechanism. ► Increasing friction will change the deformation mode of the rivet. The present paper investigates the fracture mechanisms of AA7278-T6 aluminium self-piercing rivets under compression during the riveting process. First, a microstructure investigation was conducted to disclose the grain structure and the particle distribution of the extruded aluminium alloy. Transmission electron micrographs revealed precipitate free zones along grain boundaries. Uniaxial tensile tests in three different directions with respect to the extrusion direction revealed anisotropy of the alloy in strength and ductility and a change in fracture mode with tensile direction. The behaviour of the alloy under compression was studied experimentally using upsetting tests and self-piercing riveting tests. Micrographs of the deformed specimens provided insight into the influence of the microstructure on the deformation and fracture of the alloy under compression. Second, numerical analyses were carried out using a 2-D axisymmetric model in LS–DYNA in an attempt to investigate the role of different physical variables on the final failure of the rivet. The numerical results revealed that constituent particles, precipitate free zones, and friction between the rivet and plates are important for strain localisation and fracture in the rivet.